How Vulnerable are Arab Countries to Global Food Price Shocks? - Ianchovichina, Elena I.; Loening, Josef L.; Wood, Christina A. (Taylor and Francis, 2014)
We estimate pass-through effects of international food price movements into domestic food prices for 18 countries in the Middle East and North Africa, using threshold regressions. International price movements transmit to various degrees into domestic prices. Transmission is mostly asymmetric, pushing domestic price levels up as increases in international food prices are typically passed through, but declines are rarely transmitted. This situation is indicative of policy and market distortions, notably the presence of food subsidies in the context of fiscal constraints. Hence, both international prices and their volatility matter for domestic inflation, yet domestic factors also play a role.